THE AGRARIAN RENTIER POLITICAL ECONOMY: Land Concentration and Food Insecurity in Colombia - Richani, Nazih (Latin American Research Review, 2012)
Why is Colombia, a country with fertile arable lands, increasingly importing its food supply as a consequence of shrinking lands dedicated to crop production, whereas land inappropriate for pasture and livestock has been expanding exponentially? The answer lies in the land laws approved since the 1930s, coupled with the state's economic policies, which have reduced the opportunity costs of investing in this sector. Both have provided an institutional matrix to transform parts of the rural economy from food production to a rentier political economy spearheaded by cattle ranching. This article explains why cattle ranching has become increasingly prominent since the 1950s for a segment of the dominant classes that is predisposed to invest in this endeavor despite the risks and low economic returns. More important, the article explains how the institutional matrix (laws and policies) and precarious property rights in rural areas provided the incipient narco-bourgeoisie, since the mid-1970s, with a pivotal incentive to choose cattle ranching as a favorite means to launder money, speculate, and exercise political power, consequently cementing rentier capitalism. Este artículo enfrenta el enigma de por qué Colombia, un país de tierras fértiles y cultivables, progresivamente importa más y más sus suministros de alimentos como consecuencia del recorte de tierras dedicadas al cultivo; mientras que tierras inadecuadas para pastos y ganado se han expandido de manera exponencial. Se argumenta aquí que las leyes de tierras aprobadas desde los años treinta, junto con las políticas económicas del estado, han reducido el costo de oportunidad de inversión en este sector. Ambas proporcionaron una matriz institucional para convertir parte de la economía rural, basada en la producción de alimentos, en una economía política rentista, encabezada por la ganadería. Esto explica por qué la ganadería se ha incrementado prominentemente desde los años cincuentas por parte de un segmento de clases dominantes predispuestas a invertir en esta operación a pesar de los riesgos y la baja rentabilidad. Más importante aún, este artículo explica cómo esta matriz institucional (de leyes y políticas) y los derechos de propiedad precarios otorgados en zonas rurales proporcionaron a la incipiente narco-burguesía, a partir de mediados de los setenta, un incentivo decisivo para elegir la ganadería como uno de sus principales medios de blanquear dinero, especular, ejercer poder político y consecuentemente consolidar el capitalismo rentista.